Urban Tourism In Kashmir Valley: An Assessment Of Srinagar City - Ul Ain, Qurat; Ahmad Bhat, Mukhtar (International Journal of Psychosocial Rehabilitation, 2020)
Urban tourism, stimulated by historical and cultural attractions has attained enormous significance in the contemporary dynamics of tourism. A term, urban tourism is generally referred to as encompassing multiple tourist activities where in cities have begun to emerge as the main destinations and places of attraction. Tourism within cities is strongly connected with their growth and technology development as well as roads, transportation, and railway. In this context, India owing to its rich and potential urban tourism along with the living of almost one-half of its population in urban areas assumes supreme importance. Within India, however Kashmir Valley whose entire economic base is based on tourism is in itself a very special case to look into. However, the general misperception regarding tourism in Kashmir Valley prevalent in academic writings is that it is taken to be an overwhelmingly rural phenomenon. This article rather makes a case for urban tourism, since most of the tourist destinations are located in urban areas. In doing so, the article identifies various research objectives; (I) examining the case of Srinagar being the main urban city of valley; (II) critical assessment of urban tourism in Srinagar in general; (III) evaluate its potentials and problems; and (IV) a modest attempt to look into the future prospects of tourism in Srinagar city by providing a way forward. The proposed outcome of this article while examining the viewpoint from various stakeholders especially, tourists, entrepreneurs and locals of the area, would be a comprehensive policy paper encompassing the aforementioned research objectives.